K-Pop as a Popular Culture Influencing Indonesian Student’s Lifestyle - Novianty, Restu Dinda; Srimulyani, Nunuk Endah (CV. Era Digital Nusantara, 2024)
This research examines the impact of the Korean Wave (K-Pop) on the lifestyle of Indonesian students, with a focus on the aspects of music, drama, and Korean pop culture trends from some existing research. South Korea, through its wave, has created a cultural phenomenon that not only encompasses entertainment but also influences various aspects of student life. The study identifies that the influence of K-Pop extends beyond music, penetrating into students' clothing styles, daily language usage, and even consumptive behavior. Students, as an active group following the developments in Korean pop culture, experience significant impacts on their lifestyle. The growth of Korean culture in Indonesia creates a distinctive identity and lifestyle among students, reflected in clothing patterns, hairstyles, and daily language inspired by Korean culture. This research employs a qualitative descriptive approach to gain in-depth understanding of how K-Pop influences students' lifestyles. By integrating findings from various previous studies, this research examines positive impacts such as increased knowledge and expanded social circles, while also noting negative effects such as consumerism and changes in student behavior. The importance of increasing students' self-awareness and self-control regarding cultural influences, promoting local culture by educational institutions, instilling consumer education, and raising awareness of the role of social media in shaping students' perceptions of lifestyle is emphasized. Thus, it is hoped that students can wisely utilize cultural influences while maintaining their local cultural identity.